Correlated factors to mother's accuracy in providing complementary feeding - Anggi Kusuma; Rini Palupi; Tri Yani Wantari (Universitas Aisyah Pringsewu, 2023)
Food or drink containing nutrients that is provided to babies or children aged 6 to 24 months to meet nutritional needs other than breast milk is known as complementary food for breastfeeding. The destructive impact that can be caused by dietary problems on 1000 first day of birth is the high prevalence of malnutrition in toddlers in Indonesia. The genesis of undernourished toddlers is 17.7%, stunting is 30.8%, and 10.2% are underweight. The research objective was to determine the correlated factors related to the accuracy of mothers in providing complementary feeding at the working area of the Public Health Center of Kalibalangan of North Lampung Regency 2021. Analytical investigation utilizing a cross-sectional approach was employed. The population in this study included 400 women with infants aged 4 to 12 months at the working area of Kalibalangan the Public Health Center of North Lampung Regency 2021. The sample in this research amounted to 80 infants. The sampling technique used was random cluster sampling. Univariate and Bivariate analysis with Chi-Square test. The results showed that most of the 61.2% (49 people) mothers had good knowledge about complementary feeding. While 65% (52 people) did not work, 66.2% (53 people) had advanced education (Senior high school, Diploma, High School), and 57.5% (46 people) of mothers are correct in giving complementary feeding. There is a correlation between the mother's knowledge and the mother's accuracy in providing a complementary feeding p-value of 0.000. There is a correlation between the mother's work and the mother's accuracy in giving complementary feeding p-value is 0.008. There is a correlation between the mother's education and the mother's accuracy in providing complementary feeding, with a p-value of 0.016. It is advised that communication, information, and education programs be improved, particularly for pregnant women and mothers with infants aged zero to six months. Abstrak: Makanan pendamping ASI adalah makanan atau minuman kaya gizi yang diberikan kepada bayi atau anak usia 6 sampai 24 bulan untuk melengkapi ASI. Tingginya frekuensi gizi buruk pada balita di Indonesia merupakan salah satu akibat buruk dari kesulitan gizi pada masa 1000 HPK. Kejadian balita gizi kurang sebanyak 17,7%, stunting 30,8% dan 10,2% balita dalam kondisi kurus. Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan ketepatan ibu dalam memberikan MP-ASI di Wilayah Kerja Puskesmas Kalibalangan Kabupaten Lampung Utara tahun 2021. Jenis penelitian yang digunakan adalah penelitian analitik dengan pendekatan cros sectional. Populasi dalam penelitian ini adalah ibu yang memiliki bayi 4-12 bulan di Wilayah Kerja Puskesmas Kalibalangan tahun 2021 dengan jumlah 400 orang. Sampel dalam penelitian ini berjumlah 80 bayi. Teknik sampling yang digunakan cluster random sampling. Analisa Univariat dan Bivariat dengan uji Chi Square. Hasil penelitian didapat sebagian besar 61,2% (49 orang) pengetahuan ibu baik tentang MP-ASI, 65% (52 orang) ibu tidak bekerja, 66,2% (53 orang) ibu memiliki pendidikan lanjut (SMA, Diploma, PT), 57,5% (46 orang) ibu tepat dalam pemberian MP-ASI. Terdapat hubungan antara pengetahuan ibu dengan ketepatan ibu dalam memberikan MP-ASI dengan p.value sebesar 0,000. Terdapat hubungan antara pekerjaan ibu dengan ketepatan ibu dalam memberikan MP-ASI p.value yaitu 0,008. Terdapat hubungan antara pendidikan ibu dengan ketepatan ibu dalam memberikan MP-ASI dengan p.value sebesar 0,016. Disarankan untuk meningkatkan program komunikasi, informasi dan edukasi (KIE) khususnya tentang makanan pendamping ASI pada ibu-ibu hamil maupun ibu yang mempunyai bayi umur 0-6 bulan